2008
DOI: 10.1080/03079450802272945
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fluoroquinolone treatment on MDR1 and MRP2 mRNA expression inEscherichia coli-infected chickens

Abstract: Current knowledge about the expression of ABC transport proteins suggests that their expression is regulated by a variety of factors, including pathological conditions, and in particular inflammatory reactions to infection. As ABC transporters are major determinants of absorption, distribution and excretion of many antimicrobials, modulation of their activity may result in increased or decreased tissue levels of drugs, affecting the efficacy of treatment. As fluoroquinolones have been identified as modulators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Single-stranded cDNAs were synthesized and real time PCR was performed, as described previously [16].Negative controls involved omission of RNA from the reverse transcription reactions and amplifications with specific primer/probe sets to confirm the lack of genomic DNA contamination. Primers specific for abcb1 , CYP3A and β-actin were designed as described [1], [17] and commercially synthesized for real-time PCR analysis. Broiler β-actin was chosen as a housekeeping gene for normalization, based on experiments showing stable expression of β-actin mRNA in the small intestine, liver and kidney of broilers.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Single-stranded cDNAs were synthesized and real time PCR was performed, as described previously [16].Negative controls involved omission of RNA from the reverse transcription reactions and amplifications with specific primer/probe sets to confirm the lack of genomic DNA contamination. Primers specific for abcb1 , CYP3A and β-actin were designed as described [1], [17] and commercially synthesized for real-time PCR analysis. Broiler β-actin was chosen as a housekeeping gene for normalization, based on experiments showing stable expression of β-actin mRNA in the small intestine, liver and kidney of broilers.…”
Section: Methodsmentioning
confidence: 99%
“…Fluoroquinolones have been successfully used to treat colibacillosis in poultry, among which enrofloxacin is most frequently applied [1]. Pharmacokinetic studies of enrofloxacin, which were performed in pets and food-producing animals under healthy conditions via various routes of administration, show that enrofloxacin exhibits good absorption, high bioavailability, large volume of distribution and low protein-binding [2], [3], [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As intestinal BCRP limits systemic exposure to xenobiotics, alterations in the function and expression of this transporter could account for part of the variation in oral drug absorption. Studies have shown that several factors such as disease (Haritova et al ., ), age (de Zwart et al ., ) and dietary flavonoids (Imai et al ., ; Ahmed‐Belkacem et al ., ) affect the expression levels of BCRP. While expression of BCRP has been extensively investigated in rodent and human tissues, little information is available about its expression in chicken tissues.…”
Section: Introductionmentioning
confidence: 99%